Agricultural dust explosions in 1997 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
There were 16 dust explosions reported in the U.S. in 1997 according to Robert W. Schoeff, Professor Emeritus, Kansas State University, and Ralph Regan, Safety Director, USDA-FGIS. This compares to 13 in 1996 and a ten-year average of 13 explosions.
Keywords: Grain dust; Dust explosions